Effects of Drawing Direction and Angle on Stability of Point-To-Point Drawing Task Varying Length of Drawing for the Elderly - Kuo-Chen Huang; Wen-Te Chang (Bright Institute, 2022)
The aim of the present study was to show the effects of drawing direction (top-down vs. bottom-up) and angle of trace participant drew (0 vs. 60 vs. 300) on stability varying length of drawing (5.7 cm vs. 11.4 cm vs. 17.1 cm) for the elderly. These three independent variables were within-subject factors. Thirty-eight older adults (18 females, 20 males; mean age = 71.7, SD = 5.5) participated in the study. The drawing task was performed on a computer with touch screen, using an electronic pen. Drawing performance was analyzed using a 3-way repeated measures ANOVA model. Results indicated that the error for top-down was significantly larger than that for bottom-up condition; the error for the length of drawing at 5.7 cm was larger than those at 11.4 cm and 17.1 cm. Data analysis also revealed that the effect of drawing direction on drawing velocity, indicating that drawing velocity for bottom-up was significantly greater than that for top-down condition. Additionally, the drawing velocity of length of drawing was significantly greater for 17.1 and 11.4 cm than it was for 5.7 cm. The angle of trace participant drew also significantly affected drawing velocity: 60 yielded significantly greater velocity than did 0 and 300 conditions. These results have implications for product and interface design for the elderly.